Electroabsorption Modulated Lasers With High Immunity to Residual Facet Reflection by Using Lasers With Partially Corrugated Gratings - Puspa Devi Pukhrambam; San Liang Lee; Gerd Keiser (IEEE Photonics Journal)
Residual facet reflection can significantly degrade the performance of electroabsorption modulated lasers (EMLs) operating at high data rates. This issue also complicates the fabrication and characterization of the highly demanded light sources for optical interconnects and transmission. It is desired to optimize the device structure to make EMLs robust and immune to residual facet reflection. EMLs with a partially corrugated-grating DFB section are designed and optimized to have much improved tolerance to the residual optical reflection from the modulator output facet. By designing the laser section with an appropriate grating length and linear gain coefficient, the EML can have good tolerance to residual facet reflection. The analysis indicates that 100% yield can be obtained with the optimal design. If the EML needs to operate over a wide ranges of gain coefficient and facet reflection, >70% of yield can still be obtained.